2016
DOI: 10.1152/japplphysiol.00997.2015
|View full text |Cite
|
Sign up to set email alerts
|

Hindlimb unloading: rodent analog for microgravity

Abstract: The rodent hindlimb unloading (HU) model was developed in the 1980s to make it possible to study mechanisms, responses, and treatments for the adverse consequences of spaceflight. Decades before development of the HU model, weightlessness was predicted to yield deficits in the principal tissues responsible for structure and movement on Earth, primarily muscle and bone. Indeed, results from early spaceflight and HU experiments confirmed the expected sensitivity of the musculoskeletal system to gravity loading. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
154
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 198 publications
(159 citation statements)
references
References 125 publications
3
154
0
2
Order By: Relevance
“…It was also found that there were significant decreases in the absolute mass of gastrocnemius and quadriceps muscles, increases in atrogenes, MuRF1 and Atrogin‐1, and a significant decrease in muscle protein synthesis on days 7 to 14 . There are numerous other reports in the literature reporting significant bone and muscle loss with the hindlimb‐suspension model with as little as 14‐day suspension …”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…It was also found that there were significant decreases in the absolute mass of gastrocnemius and quadriceps muscles, increases in atrogenes, MuRF1 and Atrogin‐1, and a significant decrease in muscle protein synthesis on days 7 to 14 . There are numerous other reports in the literature reporting significant bone and muscle loss with the hindlimb‐suspension model with as little as 14‐day suspension …”
Section: Introductionmentioning
confidence: 84%
“…The pieces of tape were attached to a string used to suspend the mice to a metal bar across the top of the cage. Strings were adjusted to support the mouse at approximately 30 degrees of elevation, which has been previously described as adequate elevation for consistent hindlimb unloading while avoiding unnecessary strain on the animals . The mice were housed two mice per cage; however, the tethering system of the hindlimb‐suspension cage prevented physical contact between the animals.…”
Section: Methodsmentioning
confidence: 99%
“…However, to bypass the ethical and logistical issues associated with human model, a rodent model was developed in 1970s in which hindlimbs are suspended in the air to simulate microgravity while forelimbs are weight bearing . This condition results in cephalic fluid shift and unloading of the hindlimbs (hindlimb unloaded model; HU), which mimic microgravity‐induced muscle loss . Furthermore, the HU model facilitates manipulations and interventions without extensive precautionary measures required for space‐based experiments .…”
Section: Introductionmentioning
confidence: 99%
“…Typically, the HU rodents are killed 15‐60 minutes after reloading, whereas the spaceflight rodents were killed 8‐11 hours after landing on earth. Prolonged time span between reloading and tissue collection might mitigate or mask some of the spaceflight effects . Furthermore, the skeletal muscles of humans, mice and rat differ in their contractile properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation